LGBTQIA+ representations in advertising studies: um olhar sobre a produção científica brasileira do Intercom, Compós e Pró-Pesq PP de 2000 a 2020 (Intercom - Brazilian Journal of Communication Sciences, 2022)
The purpose of this article is to report and discuss the results of an analysis carried out on the development of scientific production of communicational studies in Brazil, from 2000 to 2020, which addresses LGBTQIA + representations in advertising. As sources, we considered works published in the annals of three important national events in the field of Communication Sciences, such as: Intercom/ Thematic Division (DT) 2 - Advertising and Propaganda; the Pró-Pesq PP; and Compós. From the 4,902 articles that make up the aforementioned annals, 38 (0.78%) relevant texts were identified, selected and analyzed. The results shared in this work outline an informative framework that highlights not only theoretical aspects and methodological approaches but also some paths and challenges to be embraced in future studies.
Keywords: Advertising; Representations; LGBTQIA; Scientific research